Site-specific water relations and stomatal response of Quercus ilex in a Mediterranean watershed - Sala, Anna; Tenhunen, John D (Tree Physiology, 1994)
Intraspecific variations in the water relations and stomatal response of Quercus ilex L. were analyzed under field conditions by comparing trees at two locations within a Mediterranean watershed (l'Avic, Catalonia, NE Spain). Distinct environmental gradients exist between the two sites (referred to as ridge top at 975 m and valley bottom at 700 m) with greater soil depth for water storage, reduced radiation, reduced wind and higher water vapor pressure deficits at the valley bottom than at the ridge top. Osmotic adjustment and changes in tissue elasticiity did not significantly increase drought resistance in the trees studied. The leaf-to-air vapor pressure difference (Δw) threshold for inducing stomatal closure was higher at the ridge top (15.6 kPa MPa−1 ± 0.5 SE) than at the valley bottom (9.8 kPa MPa−1 ± 1.0 SE). However, increases in Δw beyond the threshold were followed by greater reductions in leaf conductance of trees at the ridge top than at the valley bottom. At both sites, maximum leaf conductance was related to predawn shoot water potential which, in turn, was related to watershed stream flow. The effects of water deficits during the dry summer of 1989 were more severe in trees at the valley bottom than at the ridge top. During periods of high evaporative demand, site-specific differences in the control of water loss led to more conservative water use by trees at the ridge top and, thus, to even greater drought avoidance (higher predawn water potentials) in late summer.
10.1093/treephys/14.6.601
Keywords: Mediterranean sclerophylls; oak forest; oak watershed; Osmotic potential; Stomatal conductance; water potential